Influence of Building Information Modelling (BIM) on a Projects’ Success - Sanda Mărioara NAȘ; Corina RĂDULESCU; Virgil Mihai Gh.M. RĂDULESCU; Gheorghe M.T. RĂDULESCU; Mircea BONDREA; Adrian T.Gh.M (Communications of International Proceedings, 2020)
The construction project, due to its complexity, often faces difficulties in the timely implementation of all activities, without interventions or modifications on them. Also, the realization of a construction involves the work of a large team of specialists and the collaboration of large categories of stakeholders. These are subject to new requirements and regulations, which have appeared periodically, related to safety conditions, quality, maintenance, etc. BIM is a concept that proactively responds to these challenges by improving the way buildings are designed, built and monitored. This paper suggests that BIM is a viable alternative to successfully implementing a complex project, due to the advantages created by the high-performance information system on which it is based. The research aimed to analyse the correlation between BIM performance factors and ensuring the success of construction projects. The analyse was performed by a survey applied on the managers in the construction sector from North-western Romania, who intend to implement, or have implemented BIM based construction projects. The study shows a positive correlation only with some of the BIM performance variables with the success of the project, suggesting the idea of a poor perception of managers in the studied area on the benefits of using BIM technology in construction projects.
Keywords: Building Information Modelling; Construction Projects; success factors.